(Table T1) Relative abundance of diatoms in ODP Hole 169-1034B sediments - Elisabeth Fourtanier; John A Barron (PANGAEA, 2000)
Ocean Drilling Program (ODP) Site 1034 (48°38.000 extquotesingleN, 123°30.000 extquotesingleW) was drilled at a water depth of 200 m in the Saanich Inlet, an anoxic fjord on the southeastern coast of Vancouver Island, British Columbia, to a depth of 118.2 meters below seafloor (mbsf). The uppermost 50 m consists of very well-laminated (triplet varves) diatomaceous muds deposited over the past 7000 yr. Below, sediments become progressively less distinctly laminated and reflect better oxygenated bottom-water conditions. The oldest sediments recovered at Site 1034 were dated as 14 to 15 ka (see Shipboard Scientific Party, 1998, doi:10.2973/odp.proc.ir.169s.1998). Varved sediments recovered during Leg 169S in the Saanich Inlet offer an excellent opportunity to compare the interannual variability of recent climatic elements (e.g., sea-surface temperature, salinity, precipitation) with those of late Quaternary periods that were characterized by climates appreciably different from those of today. A large amount of recent diatom data from Saanich Inlet exists, which can serve as a baseline for such comparisons: Sancetta (1989a, doi:10.1029/PA004i003p00235; 1989b, doi:10.1093/plankt/11.3.503; 1990) investigated modern processes controlling the accumulation of diatoms and spacial and temporal trends of diatom flux in the Inlet; Sancetta and Calvert (1988, doi:10.1016/0198-0149(88)90058-1) documented the annual cycle of sedimentation in the fjord. McQuoid (1995) and McQuoid and Hobson (1997, doi:10.1093/plankt/19.2.173) studied the modern pattern of diatom succession in the Saanich Inlet and analyzed the diatoms in laminae couplets in frozen sediment cores for the years 1900 to 1991 A.D. This report describes the intra-annual variability of the diatom assemblages at Site 1034, during a 8-yr interval near 9 ka. Pollen and dinoflagellates are being studied from the same samples by R. Hebda and P. Mudie (unpubl. data).
Supplement to: Fourtanier, E; Barron, JA (2000): Data Report: Intra-annual variability of the diatom assemblages at Hole 1034B (Saanich Inlet) near 9 ka. In: Bornhold, BD; Firth, JV (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 169S, 1-8, https://doi.org/10.2973/odp.proc.sr.169S.195.2000